Responses of the Endophytic Bacterial Communities of Juncus acutus to Pollution With Metals, Emerging Organic Pollutants and to Bioaugmentation With Indigenous Strains - Syranidou, Evdokia; Thijs, Sofie; Avramidou, Marina; Weyens, Nele; Venieri, Danae; Pintelon, Isabel; Vangronsveld, Jaco; Kalogerakis, Nicolas (Frontiers in Plant Science, 2018)
Plants and their associated bacteria play a crucial role in constructed wetlands. In this study, the impact of different levels of pollution and bioaugmentation with indigenous strains individually or in consortia was investigated on the composition of the endophytic microbial communities of Juncus acutus. Five treatments were examined and compared in where the wetland plant was exposed to increasing levels of metal pollution (Zn, Ni, Cd) and emerging pollutants (BPA, SMX, CIP), enriched with different combinations of single or mixed endophytic strains. High levels of mixed pollution had a negative effect on alpha diversity indices of the root communities; moreover, the diversity indices were negatively correlated with the increasing metal concentrations. It was demonstrated that the root communities were separated depending on the level of mixed pollution, while the family Sphingomonadaceae exhibited the higher relative abundance within the root endophytic communities from high and low polluted treatments. This study highlights the effects of pollution and inoculation on phytoremediation efficiency based on a better understanding of the plant microbiome community composition.